Perancangan Aplikasi Human Resource Information System (HRIS) Berbasis Website (Studi Kasus: PT. Bintang Mitra Pratama) - Abimanyu, Yuliansyah; Nugroho, Fajar Agung (Universitas Pamulang, 2023)
A company's human resources (HR) department is a crucial component. Data administration in organizations with a big number of people, like PT. Bintang Mitra Pratama, is manual (using Microsoft Excel) and appears disorganized, which results in a variety of issues, including: Because the files are not arranged effectively, it is challenging to access personnel information (employee name, division, position, and work status). Payroll results then accumulate and become obscure. A Human Resources Information System (HRIS) application was developed to address these issues. which, via the stages of planning, modeling, implementation (construction), and testing, may assist the persons / HRD and staff in producing reports and data collecting that is neater and more accurate. The Waterfall method has multiple active stages as it develops: requirements.